When Knowing is Not Enough - the Relevance of Teachers' Cognitive and Emotional Resources for Classroom Management - Johanna Seiz; Thamar Voss; Mareike Kunter (EARLI, 2015)
This study expands the discussion on teacher competence by investigating the relevance of teachers' combined cognitive resources and emotional resources for effective classroom management. While research on teacher qualification stresses the importance of knowledge for effective teaching, research on teacher stress focuses on their emotional functioning, often without connection to their in-class behaviour. Drawing on findings from health psychology showing that high levels of emotional exhaustion can impair cognitive performance, we hypothesised that teachers' pedagogical/psychological knowledge would predict their classroom management behaviour only when their level of emotional exhaustion was low. We administered a test to assess the pedagogical/psychological knowledge of 205 secondary school teachers, measured their emotional exhaustion, and assessed their classroom management using ratings of their 4,672 students obtained one year later. Data were analysed using latent moderation analyses, a novel statistical approach that rarely has been employed in research on learning and instruction. Our findings confirmed our hypotheses and indicated an interaction between teachers' cognitive resources and emotional resources, which together predict their classroom management behaviour. Thus, the new theoretical and empirical integration of two distinct areas of teacher quality broadens our understanding of teacher resources necessary for effective instruction. We argue that teacher education should acknowledge the interplay of the different resources teachers have and help them develop their emotional resources to ensure effective instruction.